Development of a framework for genotyping bovine-derived Cryptosporidium parvum, using a multilocus fragment typing tool - Hotchkiss, Emily J.; Gilray, Janice A.; Brennan, Marnie L.; Christley, Robert M.; Morrison, Liam J.; Jonsson, Nicholas N.; Innes, Elizabeth A.; Katzer, Frank (BioMed Central, 2015)
Background: There is a need for an integrated genotyping approach for C. parvum; no sufficiently discriminatory scheme to date has been fully validated or widely adopted by veterinary or public health researchers. Multilocus fragment typing (MLFT) can provide good differentiation and is relatively quick and cheap to perform. A MLFT tool was assessed in terms of its typeability, specificity, precision (repeatability and reproducibility), accuracy and ability to genotypically discriminate bovine-derived Cryptosporidium parvum.